A Prevention Initiative to Reduce Healthcare-Associated Bloodstream Infections in a Spanish University Hospital. (October 2020) - Posso, Margarita; Hidalgo-Lopez, Carlota; Civit, Anna; Lafuente, Elisabeth; Montero, a Milagro; Horcajada, Juan P.; Castells, Xavier; Juanes, Cristina Gonzalez
Abstract : Background: Bloodstream infections are one of the main adverse effects of healthcare in Spain. In our hospital, we have reported that the mean incremental cost of patients who develop bacteremia during admission was €15, 526 (US18, 314.62) per discharge, representing an annual increment in hospital cost of €1, 108, 190 (US1, 307, 232) in 2005–2012. Moreover, we have also observed that only 15.4% of episodes of our bacteremia occur in intensive care units, with most of these infections (67%) occurring in conventional units. 1 Therefore, we started several initiatives to reduce healthcare-associated bloodstream infections. Herein, we describe one of these initiatives, which is the implementation of the intravascular therapy team (ITT) and its effect on the observed healthcare-associated bloodstream infections. Methods: This retrospective analysis evaluated the incidence of healthcare-associated bloodstream infections in a University Hospital of 520 beds from January 2014 to June 2019. The ITT was implemented in 2017. This is a multidisciplinary team with 2 specialists in infection control and 2 specialists in intravascular therapy. We evaluated the annual incidence rate of healthcare-associated bloodstream infections (number of bacteremia episodes per 1, 000 days of hospital stay) and its relation with the interventions carried out by the multidisciplinary team. Results: The annual incidences of healthcare-associated bloodstream infections (episodes per 1, 000 days of hospital stay) were 0.50 (2014), 0.46 (2015), 0.58 (2016), 0.69 (2017), 0.60 (2018), 0.51 (first quarter 2019), and 0.38 (second quarter 2019, 0.38), respectively. The highest incidence of bacteremia was observed in 2017 when the ITT started the following actions: (1) following a clinical protocol to improve the appropriateness in the utilization of new devices such as a peripherally inserted central catheter (PICC) and Medline; (2) continuous training of healthcare professionals, particularly young staff; (3) feedback with hospitalization units; and (4) proactive surveillance of venous access manipulation and maintenance. The interventions were designed, implemented, and evaluated by the ITT and were well accepted by healthcare professionals. After the implementation of the ITT, the incidence of healthcare-associated bloodstream infections decreased. This trend was particularly relevant for parenteral nutrition catheters (episodes per 1, 000 days of parenteral nutrition) (Fig. 1). Conclusions: The implementation of the ITT in our center has allowed us to considerably reduce the incidence of healthcare-associated bloodstream infections. From our experience, the interventions related to systematic evaluation, education, and feedback are key to obtain and maintain this improvement. Funding: None Disclosures: Carlota Hidalgo-Lopez reports that this study was partly funded by Diversey. The authors did not receive direct Funding: from the sponsor, Juan Pablo Horcajada reports consulting fees from MSD, Pfizerand, and Menarini, as well as speaker fees from MSD, Pfizer, and Zambon.